2017
DOI: 10.1016/j.jbusres.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of foreign brand communication: Consumer culture ad imagery and brand schema incongruity

Abstract: Drawing from international branding literature and schema incongruity research, the present study (a) assesses foreign brand communication effectiveness by juxtaposing three alternative advertising approaches based on local, foreign and global consumer culture imagery, and (b) investigates the mechanism underlying consumers' responses to foreign brand communication. In a 2 (foreign brand schema vs. control) × 3 (local vs. foreign vs. global ad type) full-factorial, between-subjects experiment with a consumer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Product quality is defined as the totality of product features and characteristics defined as the totality of features and characteristics of a product or service that can satisfy stated or implemented needs (Zhu et al, 2020). Image of Brand is a concept that is easy to understand but difficult to explain systematically because of its abstract nature; the image of the brand is related to attitudes in the form of beliefs and preferences for brands related to attitudes in the form of thoughts and intentions for a brand (Halkias et al, 2017;Huang & Liu, 2020;Kim & Yoo, 2015;Maheshwari & Yadav, 2015;Sondakh, 2015). Based on the above background, the problem formulation will be discussed in this study, namely:…”
Section: Introduction *mentioning
confidence: 99%
“…Product quality is defined as the totality of product features and characteristics defined as the totality of features and characteristics of a product or service that can satisfy stated or implemented needs (Zhu et al, 2020). Image of Brand is a concept that is easy to understand but difficult to explain systematically because of its abstract nature; the image of the brand is related to attitudes in the form of beliefs and preferences for brands related to attitudes in the form of thoughts and intentions for a brand (Halkias et al, 2017;Huang & Liu, 2020;Kim & Yoo, 2015;Maheshwari & Yadav, 2015;Sondakh, 2015). Based on the above background, the problem formulation will be discussed in this study, namely:…”
Section: Introduction *mentioning
confidence: 99%
“…In addition, an interesting insight was presented in a different context by Halkias et al (2016) and Halkias, Micevski, Diamantopoulos, and Milchram (2017). Halkias et al (2016) found strong interaction effects between country image and brand globalness in predicting brand preference.…”
Section: Consumer Perceptions Of Brand Globalnessmentioning
confidence: 99%
“…Halkias et al (2016) found strong interaction effects between country image and brand globalness in predicting brand preference. Similarly, Halkias et al (2017) report a finding that advertising based on global consumer culture imagery tends to produce greater brand credibility when it is linked to the foreignness of brand origin. These findings may suggest that country image may play a greater role in quality judgments for highly global brands, which are brands better known to consumers.…”
Section: Consumer Perceptions Of Brand Globalnessmentioning
confidence: 99%
“…Consumers use schemata to form brand perceptions (Halkias 2015; Meyers-Levy and Tybout 1989), to make sense of advertising messages and marketing communications (Halkias and Kokkinaki 2014), and to understand how product categories are structured in a meaningful way (Boush and Loken 1991). In empirical work, schemata have been used as theoretical vehicles to explain (1) how congruence between consumer culture ad imagery and brand image affects the effectiveness of foreign brand communications (Halkias et al 2017), (2) how consumers form stereotypes (i.e., collectively shared schemata) about brands and products based on their globalness/localness (Davvetas and Halkias 2019) or country of origin (Diamantopoulos et al 2017), and (3) how home country–brand schema congruence enhances brand evaluations (Magnusson, Westjohn, and Sirianni 2019).…”
Section: Conceptual Background and Research Hypothesesmentioning
confidence: 99%